Effectiveness of the national German quitline for smoking cessation: study protocol of a randomized controlled trial - Simone Delle; Ludwig Kraus; Simona Maspero; Oliver Pogarell; Eva Hoch; Kirsten Lochbühler (BMC, 2022)
Abstract Background Despite the decline in cigarette smoking prevalence during nearly the past two decades, tobacco use is still widespread in the German adult population, accounting for 125,000 deaths each year and causing tremendous social costs. To accelerate the reduction in tobacco smoking prevalence, evidence-based smoking cessation methods are pivotal to a national tobacco control strategy. The present study aims to evaluate the effectiveness of the national German Smokers Quitline offering cessation support to smokers. Methods A total sample of 910 daily smokers, who are motivated to quit, will be recruited via an online access panel and randomly assigned to either the intervention (telephone counselling) or control condition. In the intervention group, participants will receive up to six proactive phone calls during an intervention period of approximately six weeks. The provided treatment will combine the principles of motivational interviewing and those of the cognitive behavioural approach to treating substance use. Participants in the control condition will receive a self-help brochure to support smoking cessation. Data collection will take place at baseline as well as three (post assessment) and twelve months (follow-up assessment) after baseline assessment. Primary outcome measures will include the seven-day point prevalence abstinence at 3-month and 12-month assessments as well as prolonged abstinence (abstinence over the 12 month period). Secondary outcome measures will include a change in smoking-related cognitions and coping strategies among all participants. Among non-abstainers, treatment success indicators such as a reduction in number of cigarettes smoked per day and changes in the number and duration of quit attempts after intervention start will be assessed. It is expected that after both three and twelve months, smoking cessation rates will be higher in the telephone counselling condition compared to the control condition. Discussion The results will provide insights into the effectiveness of proactive telephone counselling by the national German Smokers Quitline. Trial registration The protocol for this study is registered with the German Clinical Trials Register: DRKS00025343, Date of registration: 2021/06/07, https://www.drks.de/drks_web/setLocale_EN.do